Evaluating DNA quality in Coleoptera and Lepidoptera: Impact of fixation and preservation in various trapping methods - Stočes, Dominik; Wijacki, Tamara; Knoll, Aleš; Kopecký, Tomáš; Šipoš, Jan (Wiley-Blackwell, 2025)
Despite advancements in barcoding and metabarcoding, preserving high-quality DNA from field-collected arthropods remains challenging. Although various fixatives and preservatives are used for DNA recovery in Coleoptera (Carabidae) and Lepidoptera (Noctuidae, Nolidae, Geometridae, and Tortricidae), their effects on DNA quality across trapping methods are not fully understood. This study evaluates fixation and preservation strategies affecting DNA integrity, focusing on pH changes before and after tissue grinding to improve consistency. For Carabidae, Calathus fuscipes (L.) were collected with a Malaise trap, while Platynus assimilis (Paykull) were collected via emergence traps and pitfall traps (with and without roof), using propylene glycol as a fixative. Preservation methods included storage in propylene glycol, 96% ethanol, or drying, with samples kept at MINUS SIGN 20oC for 1 year. Propylene glycol samples were washed with distilled water prior to grinding. Additional fixatives in individual trapping included ethylene glycol, propylene glycol, ethanol, brine, ethyl acetate, vinegar, and drying (with and without silica gel), stored at MINUS SIGN 20oC for 3 months. For Lepidoptera, specimens were categorized by size: large-Agrostis exclamationis (L.) (Noctuidae), medium-Meganola strigula (Denis et Schiffermüller) (Nolidae), Eupithecia insigniata (Hübner) (Geometridae), and small-Pelochrista caecimaculana (Hübner) (Tortricidae). Specimens were treated with chloroform (vapor and soaked) or cyanide vapors and stored at room temperature for 3 months. DNA quality was assessed through fragmentation analysis and PCR amplification of COI fragments (658, 313, and 157 bp for Coleoptera and 658, 311, and 220 bp for Lepidoptera) with Sanger sequencing. Results showed reduced DNA integrity in diluted Malaise trap samples, while distilled water washing improved readability in emergence trap samples. Brine proved a cost-effective preservative. For Lepidoptera, DNA preservation depended on sample size and fixative, with small chloroform-soaked specimens yielding non-sequencable DNA, while vapor-treated samples remained sequencable. This study offers insights to optimize DNA yield and preservation for arthropod research.
Keywords: arthropod barcoding; Carabidae; COI amplification; cyanide vapor; fragmentation analysis; molecular methods; PCR success; propylene glycol; UV LED light trap; DNA preservation